Engine exhaust plume mixing simulations for minimizing environmental emissions impact - Spanelis, Apostolos (Cranfield University, 2013)
Local air quality is one of several issues constraining the development of air- ports. Ongoing research shows that takeoff contributes considerably to the level of near airport pollution. Installation of a wind-brake system behind the runway threshold has been recently proposed as a way to accelerate natural lift-off of the exhaust plumes. This thesis aims to validate large eddy simulations (LES) for the numerical investigation of this problem, and contribute to a joint effort towards the installation of baffles in major airports. Ways to limit the enormous cost of such simulations are suggested, and methods to reduce the problem complexity are established by means of parametric analyses and staged cross-validations. In particular, wall-jet simulations are performed alongside wind-tunnel experiments. Results reveal that LES accurately predicts the baffle induced drag force, as well as scalar dispersion. One source of weakness in this study is the level of accu- racy of the numerical representation of the wind tunnel boundary layer. Lift-off of the plume was not observed within the investigated range (380 nozzle diam- eters), neither in the absence of baffles, nor in the presence of the basic baffle arrangement. Certain geometrical modifications, however, have shifted the onset of lift-off upstream enough, so that it is identified by the streamwise evolution of mean flow characteristics. An additional achievement of this work was to devise and validate a dynamic response algebraic model for the representation of the baffles in the flow. The established numerical approach, together with the baf- fle representation model is promising for the numerical investigation of the real scale situation at longer distances, up to 2000 nozzle diameters. This thesis sets a strong basis for the continuation of the research, adding to a growing body of literature regarding local air quality around airports.